(untitled) (Comprehensive Journal of Science, 2026)
blessings be upon the one sent as a mercy to all creation, our Master Muhammad (peace be upon him), upon his family, his Companions, and those who follow them in righteousness until the Day of Judgment. This study addresses the subject of reconciliation and pardon in light of the objectives of Islamic law (maqāṣid al-sharīʿah), considering them among the fundamental values upon which the Sharīʿah is founded and among the legitimate means for achieving social peace and consolidating the principles of justice and mercy. The study opens with the Almighty’s statement: “There is no good in much of their private conversation, except for those who enjoin charity, or what is right, or reconciliation between people” (Qur’an, al-Nisāʾ: 114), due to the clear indication of this verse regarding the centrality of reform and pardon in building the Muslim society. The introduction includes a presentation of the motives for choosing the topic and the scholarly issues it raises concerning the precise definition of reconciliation and pardon, the limits of their legitimacy, and their relationship to the objectives of Islamic law. It also clarifies the aims of the study, which are to highlight the maqāṣid-based dimension of these two principles and to demonstrate their importance in resolving individual and social conflicts, in addition to reviewing the most relevant previous studies related to the topic. The study adopts a foundational maqāṣid-based approach and is organized into one chapter comprising two sections: The first section: The foundational framework of the concepts of reconciliation and pardon in Islamic law, and it consists of three subsections. The first subsection is devoted to explaining the legal meaning of reconciliation and pardon, addressing in its first part their linguistic and technical definitions and highlighting the subtle distinctions between them. The second part presents the legal evidences from the Noble Qur’an and the Prophetic Sunnah that establish their legitimacy, thus confirming the deep-rooted nature of these two principles in Islamic legislation. The third part discusses the relationship between pardon and justice and their role in achieving a maqāṣid-based balance between safeguarding rights and promoting the values of mercy and benevolence. The second section examines reconciliation and pardon in light of the revealed texts and their objectives through four parts. The first part deals with the spiritual and ethical dimension of pardon and its effect on purifying the soul and realizing the objective of moral refinement. The second part discusses the problem of misusing reconciliation and pardon outside their proper legal context, especially when this leads to legitimizing injustice or enabling offenders to evade accountability. The third part presents applied models from the life of the Prophet (peace be upon him), such as the Treaty of al-Ḥudaybiyah, the Conquest of Makkah, and his pardon of his enemies, as practical evidence of the maqāṣid-based dimension of reconciliation and pardon. The section concludes, in its fourth part, with the extraction of the main lessons and insights from these Prophetic examples and clarifies ways to activate them in the contemporary context. The conclusion of the study arrives at several findings, most notably: that reconciliation and pardon are not merely abstract moral values, but rather deliberate legal enactments intended to achieve higher objectives, foremost among them the preservation of life, the maintenance of public order, and the realization of social peace. The study also affirms that legitimate pardon is governed by legal regulations that prevent it from becoming a means of undermining rights or obstructing justice. It further recommends the activation of a culture of reconciliation and pardon in contemporary societies through religious, judicial, and media institutions, and linking them to the objectives of Islamic law rather than to purely emotional or superficial usage. The study is supported by a list of authoritative sources and references in jurisprudence, maqāṣid theory, and Prophetic biography, and is appended with several scholarly indexes, such as an index of Qur’anic verses, an index of Prophetic traditions, an index of personal names, and a subject index, in order to facilitate the reader’s access to the contents of the study and to ensure academic and methodological accuracy. Thus, this study contributes to highlighting the maqāṣid-based dimension of reconciliation and pardon and affirms their role in building a society founded upon justice and benevolence, in accordance with Qur’anic and Prophetic guidance.